The Environmental Social Service: commitment to the Sustainable Development Goals and the defense of the environment as a human right - Marques, Eduardo José da Silva Tomé (2021)
The ecological crisis we are experiencing negatively affects the planet and increases threats to all forms of life that inhabit it. Social work has an important, growing and challenging field of intervention in social and environmental spaces. For this link between social work and the environment, new intellectual and cultural knowledge, new and multiple propositions and interventions are needed, and the commitment not to be left out of the discussions and actions that it needs, to intervene and promote an active ecosystem approach, based on the circular economy and aligned with the Sustainable Development Goals and human rights. The Donut model allows a systemic and holistic analysis of the problems and difficulties that professionals face, but it also allows us to reflect on the challenges and opportunities facing social workers in a time of uncertainty and increased social risks.